Considerações sobre a influência da compactação na formação do esqueleto mineral, na textura e na permeabilidade de mistura asfáltica aeroportuária. - Maia, Renan Santos (2020)
Achieving satisfactory balance between concrete asphalt (CA) volumetric and surface parameters in the field is a complex work. Thus, this paper aims to evaluate some factors of compaction processes' influence on asphalt mixtures' mineral skeleton, texture, and permeability. For this, airport dense-graded CA was constructed applying 8 different compaction protocols varying in terms of Degree of Compaction (GC) and sequence of rollers. The analysis of mineral skeleton and texture was based on Digital Image Processing (PDI) techniques: The Image Processing and Analysis Software (iPas2), the Aggregate Imaging Measurement System (AIMS2), and the Close- Range Photogrammetry (FPA). Statistical analysis pointed to the significance of the compaction process influence on macrotexture. Also, GC values greater than 96% led to permeability coefficients below the maximum limit of 1.25E-5 m/s. However, mineral skeleton, microtexture, and isotropy of texture parameters seem to depend more on particle size distribution and aggregates’ shape properties.